2019
DOI: 10.1175/jcli-d-19-0049.1
|View full text |Cite
|
Sign up to set email alerts
|

El Niño–Related Summer Precipitation Anomalies in Southeast Asia Modulated by the Atlantic Multidecadal Oscillation

Abstract: How the Atlantic multidecadal oscillation (AMO) affects El Niño–related signals in Southeast Asia is investigated in this study on a subseasonal scale. Based on observational and reanalysis data, as well as numerical model simulations, El Niño–related precipitation anomalies are analyzed for AMO positive and negative phases, which reveals a time-dependent modulation of the AMO. 1) In May–June, the AMO influences the precipitation in southern China (SC) and the Indochina peninsula (ICP) by modulating the El Niñ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…Fan et al . (2019) noted that warming of the North Atlantic during the positive phase of the AMO favours the eastward propagation of anomalous wave trains from the North Atlantic to East Asia, which has induced a high‐pressure anomaly and suppressed the precipitation over southern China and eastern Indochina Peninsula.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al . (2019) noted that warming of the North Atlantic during the positive phase of the AMO favours the eastward propagation of anomalous wave trains from the North Atlantic to East Asia, which has induced a high‐pressure anomaly and suppressed the precipitation over southern China and eastern Indochina Peninsula.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Fan et al . (2019) proposed that the Atlantic multidecadal oscillation (AMO) can modulate the early and late summer precipitation anomalies associated with El Niño in Southeast Asia. During the positive phase of the AMO, the impact of El Niño on Southeast Asian precipitation in early summer is largely reduced by the negative WNP SSTAs, while the late summer precipitation in South China and the Indochina peninsula is suppressed by the anomalous wave trains propagating along the 'great circle route'.…”
Section: Introductionmentioning
confidence: 99%
“…However, Fan et al . (2019) proposed a possible mechanism affecting the precipitation anomalies associated with El Niño in the early summer and late summer based only on observations, lacking any confirmation by numerical simulations. In addition, we found that the ENSO's relationship with the East Asian early summer monsoon (EAESM) is different from that with the EASM during the whole summer season.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the influence of Pacific SST anomalies on northeast Asia summer precipitation has been reported non-consistent during the whole summer and sometimes shows significant sub-seasonal variations (Xu et al, 2017). The El Niño-related precipitation anomalies over Southeast Asia is different between periods of early and late summer (Fan et al, 2019). Therefore, to investigate the ENSO-related winter precipitation anomaly from a monthly perspective is of great importance.…”
Section: Introductionmentioning
confidence: 99%